2011
DOI: 10.1007/s00540-011-1173-9
|View full text |Cite
|
Sign up to set email alerts
|

Human brain activity associated with painful mechanical stimulation to muscle and bone

Abstract: PurposeThe purpose of this study was to elucidate the central processing of painful mechanical stimulation to muscle and bone by measuring blood oxygen level-dependent signal changes using functional magnetic resonance imaging (fMRI).MethodsTwelve healthy volunteers were enrolled. Mechanical pressure on muscle and bone were applied at the right lower leg by an algometer. Intensities were adjusted to cause weak and strong pain sensation at either target site in preliminary testing. Brain activation in response … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…The pgACC showed increased activation specifically for FM patients, in agreement with previous findings showing that chronic pain patients do not deactivate pgACC/medial PFC and/or surrounding regions of the ‘default mode’ network as strongly as controls do (and sometimes show activation)[2; 5; 6; 12; 27; 63; 72]. Conversely, the PCC/precuneus may activate in response to pressure-evoked pain in both healthy[4; 16; 43; 65] and patient populations[27; 48; 59; 65]. The value of ‘default mode’ network regions as predictors of pain may therefore vary across pain modalities and pain patient groups.…”
Section: Discussionsupporting
confidence: 89%
“…The pgACC showed increased activation specifically for FM patients, in agreement with previous findings showing that chronic pain patients do not deactivate pgACC/medial PFC and/or surrounding regions of the ‘default mode’ network as strongly as controls do (and sometimes show activation)[2; 5; 6; 12; 27; 63; 72]. Conversely, the PCC/precuneus may activate in response to pressure-evoked pain in both healthy[4; 16; 43; 65] and patient populations[27; 48; 59; 65]. The value of ‘default mode’ network regions as predictors of pain may therefore vary across pain modalities and pain patient groups.…”
Section: Discussionsupporting
confidence: 89%
“…Neuroimaging studies using functional MRI in healthy volunteers or in patients with pain syndrome under various nociceptive stimulus provided image evidences for the involvement of the CPu in pain perception, and the CPu might be an important subcortical structure participating in nociceptive modulation [5,23]. Arginine vasopressin was found to induce ACh release from the rat CPu to participate in pain modulation [24].…”
Section: Discussionmentioning
confidence: 98%
“…The neurons in the CPu can recognize noxious thermal stimulation intensity and respond during the dynamic phase of the stimulus, and may contribute toward the behavioral response to minimize bodily harm [4]. Functional MRI studies have shown changes in the blood oxygen level-dependent CPu signal in participants following noxious stimulation of muscle and bone [5]. Furthermore, CPu stimulation has been shown to increase the pain threshold and strengthen the analgesic effect of electroacupuncture [6].…”
Section: Introductionmentioning
confidence: 97%
“…Two previous fMRI studies conducted in Japan by Uematsu et al [3] and Maeda et al [4] on normal healthy subjects help to provide data on where increased activation levels in the brain are expected in response to a painful stimulus. Both experiments used a hand held digital algometer (Pressure Algometer NPA-1, Shinko, Japan) with a 10mm diameter hemispherical probe.…”
Section: Introductionmentioning
confidence: 99%